Membangun Persepsi Nilai: Kunci Sukses Mempromosikan Destinasi Berkelanjutan di Era Media Sosial - Yayuk Yuliana; Vera Kristiana; Toni Hidayat; Fitriani Pulungan; Anugerah; Intan Pertiwi; Inggit Aprilia Utami (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2026)
This study analyzes the influence of TikTok content quality on Generation Z's sustainable tourism interest using perceived value as a mediating variable. Using SmartPLS-based Structural Equation Modeling (SEM) on 100 active TikTok user respondents, it was found that content quality has a significant positive effect on perceived value (β = 0.742; p < 0.001). Furthermore, perceived value was shown to have a strong influence on travel interest (β = 0.635; p < 0.001), while content quality also had a significant direct effect on visit intention (β = 0.312; p < 0.01). These results confirm that perceived value functions as a partial mediator that strengthens the relationship between the attractiveness of digital content and the behavioral intentions of young tourists. Managerially, these findings emphasize that destination marketing strategies must go beyond visual aspects; content must be able to communicate functional and emotional values ​​to build trust among Generation Z. By optimizing informative, creative, and relevant content, destination managers can effectively convert digital interest into concrete actions in supporting more responsible sustainable tourism.